Influence of Hemizygia bracteosa (Benth) sheet on the quality of sorghum beer "tchakpalo" produced in Benin - KONFO, Christian Tétédé; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2014)
Influence of Hemizygia bracteosa (Benth) sheet on the quality of sorghum beer "tchakpalo" produced in Benin
Keywords: Sorgho; tchakpalo; activités antifongiques; stabilisation; Hemizygia bracteosa (Benth).